The issues of developing students’ linguistic competence in learning Arabic in scholarly and methodological literature - Kadirova Kamala Salikhovna (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the main challenges and strategies in developing students’ linguistic competence in Arabic, emphasizing the phonological, morphological, syntactic, and pragmatic dimensions that are shaped by the unique features of Arabic, including diglossia and the root-and-pattern morphology. Research Methodology: The article employs a qualitative review of recent scholarly and methodological literature on Arabic language teaching. The analysis focuses on identifying recurrent obstacles and recommended pedagogical approaches highlighted in contemporary studies. Results: The findings reveal that students face persistent difficulties in mastering phonology, script acquisition, and dialectal variation. Moreover, the integration of cultural knowledge is recognized as an essential but often underemphasized component in achieving effective linguistic competence. Successful approaches reported in the literature include communicative and competency-based methods, a balanced emphasis on both Modern Standard Arabic and colloquial dialects, and the incorporation of digital learning tools to support language practice. Conclusions: The study concludes that interdisciplinary perspectives are crucial in addressing the complexity of Arabic linguistic competence. Teacher preparation and continuous professional development play a central role in ensuring effective instruction and meaningful learning outcomes. Limitations: As a literature-based study, the research is limited by the scope of available sources and lacks empirical classroom observation, which may restrict the direct generalizability of the findings. Contribution: This study contributes to Arabic language pedagogy by synthesizing recent insights and offering practical recommendations for educators and curriculum designers seeking to improve the development of linguistic competence.